Analysis of Change in Students’ Visual Acuity - Khakimovna, Karimova Mavluda; Feruza, Omonova (American Journal of Bioscience and Clinical Integrity, 2026)
This article analyzes functional changes in visibility and factors affecting it. It was noted that the long-term use of modern information technologies, an increase in visual load, incorrect lighting and a sedentary lifestyle have a negative impact on the system. The study noted that decreased visual acuity is one of the important factors affecting the effectiveness of the educational process. The importance of early detection of changes in visual function, the development of preventive measures and the improvement of hygienic conditions is also justified. The findings have scientific and practical implications in protecting youth health and preventing visual impairment.